Synthesis, Characterizations, and Recent Applications of the Silica-based Mobil Composition of Mesoporous Material: A Review - Kurji, Badoor M.; Mujtaba , Iqbal M.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Silica-based mesoporous materials are a class of porous materials with unique characteristics such as ordered pore structure, large surface area, and large pore volume. This review covers the different types of porous material (zeolite and mesoporous) and the physical properties of mesoporous materials that make them valuable in industry. Mesoporous materials can be divided into two groups: silica-based mesoporous materials and non-silica-based mesoporous materials. The most well-known family of silica-based mesoporous materials is the Mesoporous Molecular Sieves family, which attracts attention because of its beneficial properties. The family includes three members that are differentiated based on their pore arrangement. In this review, the major applications of the Mobil Mesoporous Molecular Sieves family, such as catalysts, adsorbents, and drug delivery agents, have been surveyed. Furthermore, the synthesis of the Mesoporous Molecular Sieves materials, the silica sources, the importance of templates, and the mechanisms of the synthesis are discussed herein. Members of this material family are characterized by many physicochemical properties that are closely related to their high silica content, crystalline structure, and pore arrangement. Commonly, the members of this family have large surface areas, high pore volumes, small pore sizes, and narrow and uniform particle size distributions. These properties enable numerous industrial applications and opportunities for scientific studies to further develop existing materials or manufacture new ones.